Model Dan Metode Perencanaan Pendidikan Islam Analisis Di Pondok Pesantren Modern Al Ihsan Baleendah - Saepullo, Afni Fauziyah; Arul, Arul; Khana, Muhammad Amar (Jurnal Ilmiah Wahana Pendidikan, 2024)
Planning ensures the operation of the organization and is an important factor in determining the success or failure of a program. It helps the company move toward the right destination and match its previous goals. The purpose of this study was to test the model and method of planning islamic education in the modern boarding house of al ihsan baleendah. The study involves a qualitative approach and a type of analytical descriptive research. Research indicates that educational planning is a process that involves making alternative decisions in order to achieve educational objectives in light of current social, economic, and cultural conditions. The study USES several planning models, including comprehensive planning models, target target models, financing and cost effectiveness models, and PPBS models (planning, programs, and budget systems). Resource analysis, output input analysis, economical analysis, causal diagrams, and life-cycle analysis are a few of the planning methods used. The study AIDS in islamic education planning in boarding houses and can be used as a model for other educational institutions.